Defining the possible barriers to communication with cancer patients: A critical perspective from Turkey - (:unkn) unknown (Springer US, 2013)
In this chapter, I aim to define and examine the factors that may have a negative impact on communication with cancer patients in Turkey, where a move towards a patient autonomy-centered health care service has recently been observed, although paternalism still appears to be the dominant approach shaping health care professional-patient communication. Based on case reports, research findings, legal regulations, and authors’ arguments from Turkey, I focus on a number of separate but interrelated factors and argue that all of these have the potential to become barriers to communication with cancer patients. In addition, I examine two other factors—namely, therapeutic privilege and family involvement in cancer communication—and claim that they are also strongly associated with the paternalist tradition. I conclude that neither the paternalist perspective, which can impose helplessness and silence on patients, nor the legally imposed minimalist approach, in which communication is reduced to disclosure of information, is adequate to define and meet the communication needs of cancer patients. I assert that health care professionals in Turkey need to make a fresh start by abandoning the paternalist perspective and interpreting the legal criteria as a minimal ethical framework in order to understand communication as a process of continuous interaction, in which providing support and care for the cancer patient should be paramount. © Springer Science+Business Media, LLC 2013.
Keywords: Cancer; Cultural differences; Paternalism; Therapeutic privilege